DIPLOMASI STRATEGI MARITIM PENCEGAHAN PEMBAJAKAN DI ALUR LAUT KEPULAUAN INDONESIA MENYONGSONG INDONESIA EMAS 2045 - Novitasari, Destin; Rudiyanto, Rudiyanto; Yusnaldi, Yusnaldi; Widodo, Pujo; Juni Risma Saragih, Herlina; Suwarno, Panji; Yudho Prakoso, Lukman (Universitas Muhammadiyah Tapanuli Selatan, 2024)
Piracy at sea is a crime committed by a group of people to take and seize and sabotage things related to the world of shipping, especially ships. This is one of the threats that can hinder the realisation of Indonesia's vision in welcoming the golden Indonesia 2045 considering the importance of Indonesia's maritime sector. In facing the challenges of preventing piracy in the Indonesian Archipelago Sea Route, maritime strategy diplomacy is the key. The purpose of this paper is to analyse and formulate an effective maritime diplomacy strategy in preventing piracy in the Indonesian Archipelago Sea Route (ALKI) and to examine the link between piracy prevention efforts and the long-term vision of